Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10530-009-9563-8
|View full text |Cite
|
Sign up to set email alerts
|

Canopy gaps facilitate establishment, growth, and reproduction of invasive Frangula alnus in a Tsuga canadensis dominated forest

Abstract: The primary objective of this study was to determine whether the exotic, invasive shrub, glossy buckthorn (Frangula alnus), is more abundant in canopy gaps created by logging than in uncut forests. Secondary objectives were to determine whether buckthorn abundance in gaps is related to gap size, and whether or not buckthorn exhibits advanced regeneration. The abundance of glossy buckthorn was estimated in five patch cuts and three single-tree cuts in a 90 year old eastern hemlock-eastern white pine-sweet birch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 42 publications
(73 reference statements)
4
51
0
1
Order By: Relevance
“…Similarly, water quality is high if the forest cover is high, but as more trees are removed, water quality tends to decrease Blinn 2004, Stednick et al 2004). Also, the abundance of exotic species appears to increase as the intensity of the forest use increases (Belote et al 2008, Burnham andLee 2010). The effects of disturbance on the conservation value of the forest for birds (Norris et al 2009, Twedt andSomershoe 2009) and herpetofauna (Semlitsch et al 2009, Strojny and Hunter 2010, Tilghman et al 2012, Hocking et al 2013) may be variable, but generally, the conservation value is expected to decrease as disturbance increases.…”
Section: Appendixmentioning
confidence: 99%
“…Similarly, water quality is high if the forest cover is high, but as more trees are removed, water quality tends to decrease Blinn 2004, Stednick et al 2004). Also, the abundance of exotic species appears to increase as the intensity of the forest use increases (Belote et al 2008, Burnham andLee 2010). The effects of disturbance on the conservation value of the forest for birds (Norris et al 2009, Twedt andSomershoe 2009) and herpetofauna (Semlitsch et al 2009, Strojny and Hunter 2010, Tilghman et al 2012, Hocking et al 2013) may be variable, but generally, the conservation value is expected to decrease as disturbance increases.…”
Section: Appendixmentioning
confidence: 99%
“…(Fagan and Peart 2004;Webster et al 2007), an exotic invasive shrub that is now dominant in several ecosystems in Eastern North America. Its spread is facilitated by openings in the forest canopy, even partial ones, resulting from cutting and thinning operations (Burnham and Lee 2009). It is a somewhat shade-tolerant species that out competes native species in the colonization of canopy gaps, where it tends to form a very dense mono-specific stand (Frappier et al 2004;Nagel et al 2008) limiting light availability for native tree seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnus frangula L.) is an exotic invasive shrub that is now dominant in several ecosystems in Eastern North America [1]. It is a cause for great concern among forest managers and conservation scientists, because its spread and growth are facilitated by openings in the forest canopy, even partial ones, resulting from cutting and thinning operations [2,3]. Buckthorn is generally not considered particularly shade tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…Several explanations have been proposed for this question. A first explanation is that the abundant, precocious and bird-dispersed fruit (seed) production of glossy buckthorn allows for the creation of large seed and seedling banks [2,[8][9][10]. Indeed, Mills et al [10] observed seedling densities for glossy buckthorn exceeding more than seven times that of four native shrub species combined.…”
Section: Introductionmentioning
confidence: 99%